Effects of temperature and particle size on the thermophysical properties of six plant-origin protein supplements - Kong, Dandan; Chen, Jiyuan; Wang, Hongying; He, Yong (International Journal of Agricultural and Biological Engineering, 2024)
Reasonable design of the parameters of thermal processing such as conditioning and cooling according to formula changes of pelleted feeds has always been a serious challenge for Chinese feed mills and feed equipment manufacturers. Studying the thermophysical properties of different protein feeds under different temperatures and particle sizes will facilitate the equipment design, parameter optimization, and simulation for the thermal processing of pelleted feeds. In this study, the specific heat (Cp), thermal conductivity (kb), and thermal diffusivity (α) of six plant protein supplements with three particle sizes were determined over a temperature range of 25°C-100°C. The differences in Cp, kb, and α among different feedstuffs and particle sizes were analyzed and the influences of temperature and particle size on these properties were evaluated. Results showed that the Cp, kb, and α of all the feedstuffs increased with increasing temperature and varied from 1.622 to 2.417 kJ/(kg∙°C), 0.080 to 0.362 W/(m∙°C), 6.379×10–8 to 21.984×10–8 m2/s, respectively. To rise to the same temperature, the distiller’s dried grain with solubles (DDGS) needed to absorb 3% more heat than that required for soybean meal (SBM), while the rest four feedstuffs just needed to absorb 93%-98% heat for SBM. Particle size had no significant effect on Cp for all the feedstuffs (p>0.05). However, descending trends in kb and α were observed with increasing particle size for a certain feedstuff at the same bulk density. In addition, regression equations with only statistically significant terms were developed to describe Cp, kb, and α as a function of temperature and particle size for six feedstuffs. The results can provide basic theory and data for the optimization of thermal processing parameters required for the plant-protein ingredient change in compound feed formulations. Keywords: plant protein supplement, specific heat, thermal conductivity, thermal diffusivity, particle size DOI: 10.25165/j.ijabe.20231606.7089 Citation: Kong D D, Chen J Y, Wang H Y, He Y. Effects of temperature and particle size on the thermophysical properties of six plant-origin protein supplements. Int J Agric & Biol Eng, 2023; 16(6): 263–272.